MULTI-TENANT ACCREDITATION SIMULATION PLATFORM WITH HRBAC, FEDERATED INSTRUMENT BANK, AND LLM-ASSISTED FORM REVIEW - Muhammad Reza Redo Islami Islami; Dewi Kania Widyawati Widyawati; Rima Maulini Maulini; Tri Sandhika Jaya Sandhika Jaya; Akhmad Jayadi Jayadi; Ahmad Rofi'i Rofi'i; Kurniawan Saputra Saputra (Bulletin of Network Engineer and Informatics, 2026)
The accreditation preparation process for study programs in Indonesian higher education remains largely manual, making it prone to data inconsistencies and absent audit trails. Existing information systems are generally single-tenant and do not support complex access hierarchies. In this study, we design, implement, and evaluate a multi-tenant web-based accreditation preparation simulation platform using an SDLC cycle. The platform introduces four novelty layers: (1) a multi-tenant architecture with triple-layer data isolation; (2) a four-level-scope Hierarchical Role-Based Access Control (HRBAC); (3) a centralized instrument bank for distributing accreditation instrument templates; and (4) LLM-assisted form content checking. We evaluate the platform through PHPUnit functional testing (207 test methods, 23 files) on a GitHub Actions pipeline and a System Usability Scale (SUS) study with 15 respondents from six user roles. All 207 tests passed (100%) and the mean SUS score was 83.3 (Excellent category, formative reading given n = 15). We state upfront that the LLM-assisted review is currently validated at the functional and infrastructure level only; its accuracy against accreditation rubrics has not yet been evaluated and is staged as follow-up work. Within that boundary, the combination of all four novelty layers has not been reported in any previously published accreditation system research.